Software source code : statistical modeling - Rao Althar, Raghavendra; Bhattacharyya, Siddhartha; Konar, Debanjan; Samanta, Debabrata (De Gruyter STEM, 2021)
This book will focus on utilizing statistical modelling of the software source code, in order to resolve issues associated with the software development processes. Writing and maintaining software source code is a costly business; software developers need to constantly rely on large existing code bases. Statistical modelling identifies the patterns in software artifacts and utilize them for predicting the possible issues.